(untitled) (Research, Society and Development, 2021)
The first contact of pregnant women with the health service should be based on actions based on the reception and attention to health demands, with a contribution to humanized and qualified care. The work aims to identify the meanings and perceptions of puerperal women about humanized childbirth according to the literature. It is an integrative review, this method allows to unite and summarize results of research on the perception of puerperal women about humanized and systematic childbirth, contributing to strengthen the health strategies and improvements of the nurse’s work. The data were interpreted, synthesized and conclusions were drawn from the various studies included in the integrative review. It is understood that the suffering in childbirth is mitigated with the actions of the nurse and the team, the mother has greater acceptability with health professionals, contributing strongly to the application of humanized practices. This analysis leads us to make more assertive decisions in the services offered in maternity hospitals, based on policies aimed at this audience, nursing professionals and multidisciplinary teams must be aligned with the objectives of changes in their practices in order to improve care. for women.